2018
DOI: 10.1200/cci.17.00110
|View full text |Cite
|
Sign up to set email alerts
|

Novel Health Information Technology Tool Use by Adult Patients Undergoing Allogeneic Hematopoietic Cell Transplantation: Longitudinal Quantitative and Qualitative Patient-Reported Outcomes

Abstract: PurposeHealth information technology (IT) is an ideal medium to improve the delivery of patient-centered care and increase patient engagement. Health IT interventions should be designed with the end user in mind and be specific to the needs of a given population. Hematopoietic cell transplantation (HCT), commonly referred to as blood and marrow transplantation (BMT), is a prime example of a complex medical procedure where patient-caregiver-provider engagement is central to a safe and successful outcome. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In this study, we found no significant differences in BMT Roadmap use between caregiver groups. Consistent with our previous findings in adult HSCT patients [23], the laboratory module was the most viewed and discharge checklist was the least viewed. Interestingly, adult caregivers spent significantly more time utilizing the medication and phases-of-care modules than pediatric caregivers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we found no significant differences in BMT Roadmap use between caregiver groups. Consistent with our previous findings in adult HSCT patients [23], the laboratory module was the most viewed and discharge checklist was the least viewed. Interestingly, adult caregivers spent significantly more time utilizing the medication and phases-of-care modules than pediatric caregivers.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, we recognize the limitations of our work. As previously reported in adult HSCT patients [23], caregivers also faced technological barriers related to logging into the secure hospital wireless network, which was a security requirement (i.e., being timed-out after 10 minutes and having to re-log into the application). The study population was homogeneous, including mostly female, white/Caucasian, and highly educated caregivers from a single institution.…”
Section: Study Limitationsmentioning
confidence: 99%
“…We measured patient and care partner use of the portal by recording user actions in our database and leveraged previously reported measures of portal usage for comparison [7,11,20,22,27-29]. Measures included the number of visits to each page, the number of days used, length of users’ access period, and average percent of days used during the access period.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, O’Leary found that the use of an acute care patient portal had no significant effect on patient activation scores [21]. Another study found that patient activation scores increased over time with the use of an acute care patient portal designed for patients undergoing hematopoietic cell transplantation, but not linearly, suggesting that a sweet spot of utilization may exist [22]. However, these previous studies had small sample sizes and the study results may be insufficient to characterize the association of the use of an acute care patient portal with patient activation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the app was targeted a priori for the inpatient setting, and to primarily serve as a source of patient-related information. User experience interviews highlighted the ongoing caregiving journey beyond the hospital, and the need for caregiver support in the outpatient setting, such as emphasis on caregiver-specific resources to promote caregiver health and well-being (25). The current study aimed to explore the lived experiences of BMT caregivers in the outpatient context.…”
Section: Technology-mediated Interventions For Caregivers (Bmt Roadmap)mentioning
confidence: 99%